New Rules for Corporate Governance in the United States And Germany - A Model for New Zealand? - Krackhardt, Oliver (Victoria University of Wellington Law Review, 2005)
This paper surveys the possibilities for implementing new rules for corporate governance in New Zealand. It focuses on the new rules issued in Germany (the German Code of Corporate Governance) and the United States (the Sarbanes-Oxley Act). The paper analyses both to find out which rules might be appropriate for New Zealand. It is argued that New Zealand needs to adopt a code of corporate governance in order to keep up with international developments, otherwise it risks repelling local investors and failing to attract international investors. It is concluded that most importantly New Zealand should adopt a principles-based "comply-or-explain" approach rather than strict rules, as it offers greater flexibility. The paper further concludes that many of the rules issued in Germany and the United States could improve corporate governance in New Zealand and hence should be implemented.